Associations between adductor strength; flexibility and self-reported symptoms in elite professional footballers: a case series - Light, N.; Gimpel, M.; Sparks, S.; Bowen, L.; Bruce-Low, S.; Hughes-Jones, Z. (Science and Medicine in Football, 2019)
Objectives: Measures of adductor strength, flexibility and self-reported symptoms offer insights into footballer hip/groin health. Understanding their relationship may further determine their suitability for use. Design: Clinical case series Method: Eighteen professional footballers completed two adductor squeeze tests (short and long lever), the HAGOS (sport) and Bent Knee Fall Out (BKFO); 2 days post-match, during a period of 4 months. Results: Adductor strength reduced beyond the minimal detectable change (MDC) on 16 occasions for the long-lever squeeze (MDC = 7%) and 7 occasions for short-lever squeeze (MDC = 15%). On 17 occasions, participant BKFO scores reduced beyond the MDC (21%). A relationship between both squeeze tests and HAGOS (sport) was observed explaining 12% variance for short-lever (R2 = 0.121, p = 0.006) and 7% for long-lever (R2 = 0.065, p = 0.046) tests. The BKFO showed no statistically significant (P = > 0.05) correlation to either squeeze test (rp = 0.153/0.193) or HAGOS (sport) (rp = 0.182). Conclusion: This study adds to literature surrounding monitoring of hip/groin measures in footballers. The long-lever adductor squeeze detected meaningful changes more frequently than the short-lever. Both tests shared weak, albeit statistically significant relationships with HAGOS (sport), whilst the BKFO did not. A larger prospective study is warranted to increase confidence in selecting these measures in this setting.